Dampak Kausal Pemeriksaan Pajak pada Performa Perusahaan - Muhamad Taufan Setiawan (Ministry of National Development Planning Republic of Indonesia/Bappenas, 2021)
The tax compliance problem is an imminent issue in a self-assessment taxation system in Indonesia. Tax audit is an important tool used by the tax authority to address the problem. Several studies showed that tax inspection might change the behavior of the taxpayers. Therefore, it is interesting to see how tax inspection will affect taxpayers' behavior related to their subjective measure of firms' performance. This research uses the difference-in-difference approach combine with the entropy balancing method to estimate the causal impact of tax inspection on firms’ performance. The findings showed that the inspected firms showed an increase in their perception of capital utilization which can be explained using tax evasion model or managerial benefits concept.